The Effectiveness 0f Using Monolingual Dictionary In Reading Comprehension of Eleventh Multimedia Smk N 12 Surabaya (RETAIN, 2014)
The Effectiveness 0f Using Monolingual Dictionary In Reading Comprehension of Eleventh Multimedia Smk N 12 Surabaya Difa Kharizma Yuniar English Education, Faculty of Languages and Arts, State University of Surabaya d4kharizma@gmail.com FaurisZuhri, S.Pd.,M.Hum. English Education, Faculty of Languages and Arts, State University of Surabaya Abstract The objective of this research is to find out whether there is a significant difference in the reading comprehension between the students who use monolingual dictionary and those who do not. This research is experimental quantitative research design. The researcher used a test as an instrument to answer research question. The data were taken by the scores of the students test. Therefore, the data were in the form of numbers. The population was the eleventh graders of SMK N 12 Surabaya, while the samples were class XI Multimedia 2 as the experimental group and XI Multimedia 3 as the control group. To get the data, those two groups were given tests; try out, pre-test, and post-test. From the data, the researcher calculated by using statistical computation. The researcher used t-test formula to analyze the comparison of the post-test scores between the experimental and control group in order to see the significant difference. The result of the study shows that the post-test scores of the experimental group were higher than the control group. It is proven that using monolingual dictionary is effective in reading comprehension for the eleventh graders since there is a significant difference between the scores of between they who were taught by using monolingual dictionary than they who were not. Abstrak Tujuandaripenelitianiniadalahmenemukanbahwaadaperbedaandalampemahamanmembacapasdasiswa yang menggunakankamus monolingual dansiswa yang tidakmenggunakankamus monolingual. Jenispenelitian in adalah experimental quantitative. Penelitimenggunakantessebagai instrument untukmenjawabrumusanmasalah. Data diambildarinilaihasiltessiswadalambentukangka. Populasipenelitianiniadalahsiswakelassebelas SMK N 12 Surabaya, dengansampelnyaadalahkelas XI Multimedia 2 sebagai experimental grupdan XI multimedia 3sebagai kontrolgrup. Untukmemperoleh data, keduagruptersebutdiberikantesyaitu tryout, pretesdanpostes. Data yang diperolehdiolahmenggunakaperhitungan statistic yaiturumus t-test. Hasil yang diperolehmenunjukanbahwanilaipostesdari experimental gruplebihtinggidarinilaipostes control grup. Inimembuktikanbahwapenggunaankamus monolingual efektifdalampemahamanmembacasiswakelassebelas, terlihatdariadanyaperbedaan yang signifikanpadanilaitessiswa yang menggunakankamus monolingual dansiswa yang tidakmenggunakankamus monolingual. INTRODUCTION “In order to read, students must be able to decode (sound out) and also comprehend what they read “ (Linse , 2006:69). When students decode, they just learn and know how to pronounce written words correctly. It doesn’t mean they can read. They have to comprehend what they read. Reading without comprehension is not reading. Reading comprehension is a part of learning process that should be done by students in the learning and teaching process. Being able to comprehend accurately becomes difficult for students. Majid (2005:61-62) state that some people who have efficient to read their own language cannot efficiently read the foreign language because they don’t know the language enough. That is happen when they start to find out or to know exactly the meaning of one of sentence or word in a passage but they fail. So, they cannot catch the point of the passage and they cannot answer the questions about the passage well (if there are questions). “Being able to comprehend a text accurately and at a relatively rapid rate presupposes rather extensive knowledge of vocabulary and grammar” state (Celce-Murcia, &Mcintosh in Hayati study, 2005:62). Vocabularies become very important when students read. Many students still don’t have enough vocabulary to help them to read a passage. It is an obstacle that related to the students themselves. Without having a well understand of vocabulary the process of reading might break down. Reading and vocabulary have a bilateral relationships, one is not possible without another one. Because of that problem, students need a help for their reading comprehension. The using of dictionary in reading is very helpful for students. Finding the meaning of a word can be easily found through a dictionary. When the students have a few vocabularies when they read, it can be helped by using dictionary and they will have more vocabularies. When students have a passage to read, they often don’t know more than five difficult words. Using dictionary can solve that problem. “Dictionaries have been advocated as an important aid to learners of new languages” (Jacobs, 1989:2). Dictionary is very important for students that learn foreign language; it’s kind of a bridge for their first language to the second language. Dictionary will give new information, that is the meaning of the new word and give a new vocabulary for the students. Today there are a number of dictionaries, called monolingual learner's dictionaries (MLDs), written especially for learners of English. Monolingual dictionary is a dictionary with one language, in this case is English. It can help students in reading comprehension. It will give the students the meaning of the word in reading text and it will give more knowledge in vocabulary. The monolingual dictionary gives long explanation in one language, in this case is English and it makes students understand the sentence well. Based on the finding of the previous study, there is an analogy from Atkins and Varantola (1988:22), “Monolinguals are good for you like whole meal bread and green vegetables and bilinguals, like alcohol, sugar, and fatty foods, are not, though you may like them better”. They also report that using monolingual dictionary had a better chance of success than bilingual dictionary. The learners or the students maybe feel easier and more comfortable by using bilingual dictionary but using monolingual dictionary makes they understand the language better than bilingual dictionary. Monolingual dictionary is dictionary with one language inside. In this case is English. This kind of dictionary explains the meaning of one word with the same language and long explanation. Baxter in Hayati study (2006:126) stated that a monolingual dictionary not only demonstrates definitions as alternative to the use of lexical items but also provides the means to employ definitions. It can be said that monolingual dictionary gives a complete definition that the readers’ need for unknown word. The advantages of using monolingual dictionary is the reader will have all of the information that they need about one word because of the long explanation that monolingual dictionary has. The monolingual dictionary give more detailed and information about the word, for example information about idiomatic usage, common collocations amd connotations (Laufer and Melamed, 1994:565). For very simple example the meaning of word “apple”, “Apple is a round fruit with shiny red or green skin and white flesh” (Oxford, 2011:17). For the explanation of ‘apple’ in monolingual dictionary, named Oxford dictionary the readers get complete explanation. The readers can imagine the shape, the color of apple and they will know the meaning of apple correctly. Monolingual dictionary is not just translating the word but it explains the detail of that word. So, the readers will understand in deep about the word, especially the unknown word. The other previous study is conducted by Ali (2012). The title is “Monolingual Dictionary Use in an EFL Context”, this study is about exploring the teachers’ and students’ attitudes about the use of the dictionaries. The researcher of this study found that the teachers prefer their students to use monolingual dictionaries because they will help them acquire foreign language more effectively and that the bilingual dictionaries are just for translating. METHOD Dealing with the research question, the researcher chooses experimental quantitative research design. Focus of this study is in the result that was gotten by the score of students’ test. In this design, there are two groups which are used to conduct this study. They were experimental group (XI Multimedia 2) and control group (XI Multimedia 3). Both of the two groups were given a pre-test to know their reading ability. Then the experimental group was given a treatment by using monolingual dictionary in reading comprehension. This subject of this study is the eleventh graders of SMK N 12 Surabaya. This based on some reasons. The first is about the curriculum. Reading comprehension is taught in the vocational high school, and eleventh graders are the best because they are in the middle of year that they study as vocational high school students. This is in line with the lesson that will be taught in this study. The second is about the eleventh graders are already know about dictionary and know how to use it. The instrument of this study was reading comprehension test. There were two kinds of test, pretest and posttest. But, before conducting pretest and posttest, it was tryout in order to get the appropriate of the test itself.The try-out test was tested to the students of XI Multimedia 1 SMK N 1 Banyuwangi. After the researcher got the data, an analysis for the data is needed. The independent sample t-test is used to analyze the data. The score of the whole groups will calculate using t-test formula. Because this is a quantitative research, it needs data with number. After analyzing the data, the researcher will made a general conclusion about this study. RESULTS AND DISCUSSION After administering pretest for two groups, the researcher tabulated the pretest scores of experimental and control groups, and then the Mean of experimental and control group were calculated. Based on the calculation of the scores, it was found that the Mean of the experimental group was 65.83 and control group was 65.31 and the t-value is 0.21. T-value was lower than t-table (2.00). It means that the result of the calculation is not significant or there was no significant difference of the pretest scores of both groups. From that scores and the result of the calculation, the researcher found that the students of the two groups had equal abilities in reading comprehension before the treatments were given. After administering pretest of two groups and giving the treatments for two times to the experimental group, the researcher conducted a post-test for two groups. Post-test was done to know the improvement of the students after they were given the treatment, and also to compare the result with another class which was not given the treatment The result of posttest scores of the experimental and the control group were 2420 for experimental group and 2320 for control group. The mean of posttest scores of experimental group was 80.67 and for control group were 72.5. It was clearly seen that the mean of experimental group posttest score was higher than the control group. After that the researcher calculated the t-test and the result is 4.44 for t-value. Then, the t-value was compared with t-table 0.05 level of significant, while the degree of freedom (df) is 60. T-value was higher than t-table. It means that the result of the calculation is significant or there was significant difference of the posttest scores of both groups. In other words, there is a significant improvement between those who were taught reading comprehension by using monolingual dictionary and those who were not. Since the result of the posttest scores showed that the t-value is higher than the t-table while the scores was increasing significantly, it clearly seen that there is a significant difference between they who were taught using monolingual dictionary and they who are not. It proves that using monolingual dictionary is effective for eleventh graders in SMK N 12 Surabaya to improve their reading comprehension. CONCLUSION Based on the result of this study and the calculation of the data, it can be said that teaching reading comprehension by using monolingual dictionary can improve students’ ability in comprehending the text. The student can get their improvement of reading test after being taught by using monolingual dictionary. It can be proven by showing the scores of two groups which have been investigated. The mean of posttest of the experimental is 80.67 and control group is 72.5. It was found that the t-value of the t-test (4.44) was higher than the t table (2.00). Therefore, there was a significant difference between the students who are taught by using monolingual dictionary (experimental group) and those who are not (control group). The research question of this study has been answered well. It means that the teaching reading comprehension for eleventh graders by using monolingual dictionary helps the students to comprehend the text well and reach a higher score. If the teacher is using monolingual dictionary to teach reading comprehension, the students can clearly understand the text well. In conclusion, it must be clear that using monolingual dictionary is one of the effective teaching reading tools that can be used to teach reading comprehension in the classroom. REFERENCES Ali, H. B. H. (2012). Monolingual Dictionary Use in an EFL Context. English Language Teaching, 5(7), 2-7. Ary, D., Jacobs, L. C., Sorensen, C. K., & Razavieh, A. (2010).Inroduction to Research in Education (8th Ed). USA: Wadsworth Cengage Learning. Budiantari, P. Y., Nitiasih, P. K., Budasi, I. G. (2013). Developing Authentic Reading Material for the Tenth Year Students of State Vocational High School 1 Kubutambahan. e-Journal Program Pascasarjana Universitas Pendidikan Ganesha Program Studi Pendidikan Bahasa Inggris, 1. Brown, H Douglas. (2004). Language Assessment Principles and Classroom Practices. USA: Longman. Harmer, Jeremy. (2007). Practise Of Language Teaching.Fourth (Ed). England: Longman. Hayati, A Majid., & Fattahzadeh, A. (2006). The Effect of Monolingual and Bilingual Dictionaries on Vocabulary Recall and Retention of EFL Learners. The Reading Matrix, 6(2), 125-127. Hayati, A Majid., & Pourmohammadi, M. (2005). A Comparative Study of Using Bilingual and Monolingual Dictionaries in Reading Comprehension of Intermediate EFL Students. The Reading Matrix, 5(2), 61-66. Jacobs, George M. (1989). Dictionaries Can Help Writing–If Students Know How To Use Them. Paper presented at EDRS, Thailand. Linse, Caroline T. (2006). Practical English Language Teaching: Young Learners. New York: McGraw-Hill.